Analisis Kelimpahan Bakteri Coliform pada Air Sumur Warga di Kelurahan Tanjung Selamat Kecamatan Medan Tuntungan - Almadina Septiyah; Kartika Manalu; Rizki Amelia Nasution (BIOEDUSAINS:Jurnal Pendidikan Biologi dan Sains, 2023)
This study aims to determine whether there are Coliform bacteria contained in residents' well water in Tanjung Selamat Village, Medan Tuntungan District. In this study, physical tests were carried out on samples using sensory devices, chemical tests using pH paper, and bacterial identification using the MPN test which included a prediction test using Lactose Borth media, a confirmation test using Brilliant Green Lactose Borth (BGLB) media, and a certainty test. using eosin methylene blue (EMB) media. The results of the physical test obtained 1 sample and the chemical test obtained 3 samples that met the requirements for clean water health. Meanwhile, from the MPN test, the MPN value was obtained for sample 1: 43/100 ml of water, sample 2: >2400/100 ml of water, sample 3: 60.06/100 ml of water. The difference in the number of MPN values found in the samples indicates that the samples have different levels of contamination and pollution levels. Based on the research that has been done, it can be concluded that of the three water samples taken from residents' well water in Tanjung Selamat Village, Medan District, Tuntungan was positive for Coliform bacteria. Keywords: Well water, Coliform bacteria, MPN test